2020
DOI: 10.1051/e3sconf/202019710001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of nanosecond plasma discharge on the combustion of methane air flames

Abstract: At present, development of plasma assisted ignition and combustion is a very promising research area due to its wide applications in the field of aeronautical engines and power sector. Plasma discharge can improve the combustion because it produces large number of chemically active particles which affects the chemical reaction. Simulation is an effective tool to analyze the interaction between the plasma and the flame through the implementation of plasma-assisted combustion. This study focused on three main ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Therefore, the EN value for the single pulse was about 200 Td for Case 1. In our previous study, we found that the ignition has been significantly improved at 200 Td [40]. Similar results were also observed by [41] at the same EN value.…”
Section: Electrical Characterizationsupporting
confidence: 85%
“…Therefore, the EN value for the single pulse was about 200 Td for Case 1. In our previous study, we found that the ignition has been significantly improved at 200 Td [40]. Similar results were also observed by [41] at the same EN value.…”
Section: Electrical Characterizationsupporting
confidence: 85%
“…The closed homogenous batch reactor was used for the ignition analysis. The detailed description of numerical procedure and experimental validation of extended version of mechanism has been presented in our previously published articles [22,23].…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…The mean integral value of E N in the time interval of 10 −6 was about 200 Td. This value has been previously proved to improve the combustion characteristic time of methane flame [22][23][24]. Therefore, numerical analysis of ignition characteristics has been performed by considering the electrical output of Test 2.…”
Section: Electrial Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma assisted combustion (PAC) is a prominent and evolving technology devoted to the enhancement of the combustion efficiency, by extending the lean blow out limit, improving the flame stability, and allowing for low temperature oxidation and the simultaneous reduction of nitrogen oxides (NO x ) [1,2]. PAC has great potential to improve ignition and combustion by three ways via thermal (rise in temperature), kinetic (production of excited species, electron, ions and neutral radicals) and transport (fuel decomposition and reforming) [3,4].…”
Section: Introductionmentioning
confidence: 99%